Labelled image dataset of the pressure refuelling port from an Airbus A320 - Kuang, Boyu (Cranfield University, 2023)
The dataset is for a conference publication. The file contains two types of files: - images (".jpg") - labels (".json")
Keywords: Bounding boxes'; 'Object Detection'; 'Dataset'; 'Refuelling Port'; 'Airbus'; 'A320'